Fueling Growth: Entrepreneurial Intention as a Catalyst for Village Enterprises: Memicu Pertumbuhan: Niat Kewirausahaan sebagai Katalisator Usaha Desa - Ismail Rasulong; Rini; Sentot Imam Wahjono; Samsul Rizal (Universitas Muhammadiyah Sidoarjo, 2025)
This study explores the relationships among entrepreneurial self-efficacy (ESE), entrepreneurial intention, and business performance in Village-Owned Enterprises (BUMDes) in Indonesia. Using an explanatory research design and Structural Equation Modeling (SEM) with Partial Least Squares (PLS), data from 159 respondents were analyzed to examine the direct and mediated effects of ESE on business performance. Results indicate that ESE significantly influences both entrepreneurial intention and business performance, highlighting the critical role of self-efficacy in fostering entrepreneurial intentions that ultimately enhance the performance of village-owned enterprises. These findings suggest that enhancing ESE can lead to improved business outcomes, providing valuable insights for policymakers and practitioners aiming to support the growth of village-owned enterprises in Indonesia.